An Analysis of the Usage of Various Programming Languages to Classify Whether they are Relevant, Extinct, or on the Verge of Extinction - Mohit, Apoorv; Rustagi, Sunaina (Indian Journal of Computer Science, 2023)
The first modern high level general purpose programming languages appeared over seventy years ago. Since then, with the exponential increase in the usage of different types of computer software and developments in computer hardware, numerous high level programming languages have been created for various purposes, with each language having its own relative advantages and disadvantages. Usually, specific general purpose high level programming languages are appropriate for specific applications or problems because of the nature of capabilities of the languages such as efficiency, memory consumption, expressiveness, availability of compilers, and tools etc. Newer languages incorporate significant functionalities of older languages which may serve as an â€œinspirationâ€ for it while introducing new features and functionalities. However, the creation of newer programming languages does not necessarily mean the obsolescence of older languages because of factors such as programming effort, familiarity, and popularity. However, their usage for newer and upcoming applications may eventually decrease and familiarity and popularity might consequently fade away with it. In this paper, we take a look at 38 different programming languages that have been invented and identify the least used programming languages to provide an overall estimate of the least used programming languages in todayâ€™s time and the programming languages on the verge of death